Impact of pyrite on shale gas enrichment-a case study of the Lower Silurian Longmaxi Formation in southeast Sichuan Basin - CHEN, Xin; CHEN, Lei; TAN, Xiucheng; JIANG, Shu; WANG, Chao (Frontiers of earth science, 2021)
Pyrite is one of the important components of shale and plays a crucial role in shale gas enrichment. However, currently there are just a few studies on this subject matter. Therefore, the characteristics of pyrite in organic-rich shale section of the Longmaxi Formation and its impact on shale gas enrichment was studied in this paper by using outcrops, drilling cores, thin sections and test data. Result shows that pyrite occurred in different forms (macro-micro scale) in the Longmaxi Formation in the southeast Sichuan Basin. The formation and content of pyrite has a close relation with TOC content. Pyrite may catalyze the hydrocarbon generation of organic matter. Interparticle pores within the pyrite framboids and organic matter pores in the pyrite-organic matter complex are well-developed in the Longmaxi Shale, which serves as a major reservoir space for shale gas. Pyrite can promote shale gas enrichment by absorbing shale gas on its surface and preserving free gas in the interparticle pores and organic matter pores. In addition, as a kind of brittle mineral, pyrite can improve the brittleness of shale reservoir and increase the micro-nano pore system in shale reservoir, thereby improving the transmission performance of shale reservoir and boosting shale gas recovery.